The impact of Sleep Hygiene in school-age children with ADHD - Koulafa, Ioanna (My University, 2022)
Children with Attention Deficit/Hyperactivity disorder (ADHD) of the experiencing sleeping difficulties. Sleep hygiene is defined as a set of behavioral, environmental, or cognitive modifications to improve sleep. This systematic review aimed to investigate the effectiveness of sleep hygiene in treating sleep difficulties in school-age children with ADHD. Sever relevant articles with total 2.016 participants across 5 countries. All the studies found that sleep hygiene practice is effective measure treating sleep disturbances and improving the sleep and daily quality of life in children with ADHD. However, further research is needed to strengthen the evidence.
Keywords: ADHD; Sleep hygiene; Behavioral intervention; Sleep difficulties